(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This article explores the global trends shaping the development of the tourism business, emphasizing the increasing demand for sustainability, the rise of experiential and authentic travel, technological innovations, and the impact of the COVID-19 pandemic. The study uses a mixed-methods approach, combining qualitative and quantitative data from surveys with tourism industry professionals and secondary data from key industry reports. The results reveal that sustainability, technological advancements, and consumer demand for unique experiences are driving business strategies in the tourism sector. The article highlights the adaptation of businesses to emerging trends, such as green certifications, digital tools, and the growing interest in domestic travel post-pandemic. The findings offer valuable insights into the future trajectory of tourism business development and the opportunities and challenges businesses face in a rapidly changing global landscape.